Incidence of Opportunistic Infections among Adult HIV Positive People Receiving Co-trimoxazole Prophylaxis - Yihun Tariku G; Yaliso Yaya; Degu Jerene; Alemu Tamiso (International Journal of Public Health Science (IJPHS), 2015)
In Ethiopia, Co-trimoxazole prophylaxis therapy (CPT) used to prevent opportunistic infections among people living with HIV is the standard of practice; however incidence of opportunistic infection and their predictors are rarely documented in the country.  This was a retrospective follow up study to describe the incidence and predictors of opportunistic infections among 244 adults receiving CPT. Participants were followed for a median time of 72 weeks. During a study period a total of 53opportunistic infections were recorded; making the overall incidence rate 23.9/100 person-years. High incidence of opportunistic infections is likely to occur if: the clients were married (adjusted hazard ratio (AHR) 1.965;(95% CI: 1.109, 3.451), had history of tuberculosis treatment (AHR: 2.34(95% CI:1.05, 5.24)), patients who are indicated for CPT because of both clinical and WHO clinical staging criteria(AHR 2.418 (95% CI:1.02, 5.72 ),and had poor adherence to CPT (AHR, 2.11 (95% CI: 1.19-3.72)). Eventhough adherence is non-substitutable strategy to prevent opportunistic infection, the cohort of HIV patients failed to adhere to CPT, which in turn resulthigh incidence of opportunistic infections among them, therefore improving adherence as guideline should be a priority to prevent OIs among people living with HIV in the study region.